The Impact of Electronic Word of Mouth (EWOM) Using Influencers on Brand Awareness and Purchase Intention - Santika Vania Putri (CoverAge: Journal of Strategic Communication, 2022)
Digitalization has transformed individuals’ behaviour in receiving information. The changes has encourage marketer to shift their marketing strategy, from offline to online. With the existence of internet, Word of Mouth (WOM) strategy has converted to electronic Word of Mouth (eWOM)with the help of social media. eWOM itself has an advantage of raising awareness of a product, service, or a brand itself. Adopting the eWOM concept, there comes a new marketing strategy called buzz marketing, in which usually is using a third-party to maximize the viral and trending effect from eWOM. Using a case study from a beauty brand, Secondate, this paper analyzes the buzz marketing campaign that was done by Secondate on their first launching. Instead of using a buzzer, Secondate used more than 20 Indonesian influencers to create a buzz on social media and increase brand awareness of the brand Secondate. This paper alsoexplains the benefits of using influencer in eWOM instead buzzers in terms of leveraging a brand awareness. The result of this paper is that eWOM through influencer has a positive impact in increasing brand awareness, while influencers have no significant impact in customers’ purchase intention.